PELATIHAN KOMUNIKASI BISNIS BAGI MAHASISWA DALAM MEMULAI DAN MENGEMBANGKAN BISNIS - Hidayah, Anisya Nur; Bharata, Wira; Putera, Muhammad Tommy Fimi (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
Business is one way that many people do to earn income. This fact has an impact on the large number of business actors or entrepreneurs in Indonesia. However, among the many entrepreneurs in Indonesia, students are not the biggest contributors. The existence of complex aspects in running a business is considered to be a trigger for decreased interest in doing business among students, such as business communication. Business communication is a crucial aspect because it is related to various foundations of business management, so it must be mastered to facilitate the process of starting and developing a business, especially for students. Business Communication Training activities are carried out for students with the aim of increasing knowledge related to business communication skills and raising student awareness of the importance of good communication skills in business. This activity was attended by 22 students as participants from different regions. The conclusion drawn is that Business Communication Training has a direct impact on students in increasing knowledge related to business communication skills and can raise student awareness of the importance of good communication skills in business.